"Indie Movie" Film Making Training for SMAK 2 BPK Penabur Bandung Students: Pelatihan Pembuatan Film “Indie Movie” Bagi Siswa SMAK 2 BPK Penabur Bandung - Yapinus, Pin Panji; Wijaya*, Marvin Chandra; Wong, Hendry; Loekito, Jimmy Agustian; Chandra, Jonathan; Tjiharjadi, Semuil; Lehman, Andrew Sebastian; Tanubrata, Markus (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
At this time, computer lessons at the high school level still need a variety of materials to meet the progress of today's era. Computer training in various fields is indispensable for high school students. One of the fundamentals is training in filmmaking. This training teaches skills and knowledge in the fields of exposure, shooting techniques, and lighting techniques. This training is divided into eight meetings to deliver the material properly. The trainees have been very excited to participate in this filmmaking training. The final evaluation results for the training participants are given in the form of questions and practice of making films. Based on the results of the final evaluation, it was found that the average absorption capacity of the training participants reached 75%.